Midwives' Experiences in Providing Care and Counselling to Women with Female Genital Mutilation (FGM) Related Problems - Elisabeth Isman; Amina Mahmoud Warsame; Annika Johansson; Sarah Fried; Vanja Berggren (Obstetrics and Gynecology International)
Aim. The aim of this study was to elucidate midwives experiences in providing care and counselling to women with FGM related problems. Setting. The study was conducted at a maternity clinic in Hargeisa, Somaliland. Method. A qualitative, inductive study were performed with eight midwives living in Somaliland. The interviews had semi-structured questions. Content analysis was used for the analysis. Findings. The main findings of the present study were how midwives are challenged by culture and religion when providing FGM counselling. The most prominent challenge is the perception that FGM is an important part of the culture and from this point of view the midwives work is apprehended as interfering and subverting the Somali culture. Having personal experience of FGM emerged as a benefit when counselling women. Conclusion. There is a contradiction between the professional actions of performing FGM despite a personal belief against FGM. Midwives as a professional group could be important agents of change and further research is needed about the midwives role in this process.